2005
DOI: 10.1119/1.1870032
|View full text |Cite
|
Sign up to set email alerts
|

A simple experiment on diffraction of light by interfering liquid surface waves

Abstract: Interfering liquid surface waves are generated by electrically driven vertical oscillations of two or more equispaced pins immersed in a liquid (water). The corresponding intensity distribution, resulting from diffraction of monochromatic light by the reflection phase grating formed on the liquid surface, is calculated theoretically and found to tally with experiments. The curious features of the diffraction pattern and its relation to the interference of waves on the liquid surface are used to measure the amp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…where, the factor of cos θ i appears due to oblique incidence of the incident monochromatic light [11,14,15,25]. The field strength E of the diffraction pattern can be estimated from the Fourier transform of the aperture function (in this case the surface wave produced by single exciter).…”
Section: B Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…where, the factor of cos θ i appears due to oblique incidence of the incident monochromatic light [11,14,15,25]. The field strength E of the diffraction pattern can be estimated from the Fourier transform of the aperture function (in this case the surface wave produced by single exciter).…”
Section: B Theoretical Backgroundmentioning
confidence: 99%
“…where z is the horizontal distance between the location of the laser spot on the liquid surface and the screen and Λ = When we generate capillary waves by means of a single pin exciter, the amplitude of the wave at the point of oscillation is almost the same as the amplitude of the oscillating pin in a low viscous liquid [15]. The intensities of different orders depend only on the amplitude of the capillary wave (h), if other parameters like θ i and λ are kept constant (Eqn.…”
Section: B Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…We failed to find similar stud ies as applied to systems of two immiscible liquids, although Barik et al. [2] and Boev and Yasnitskaya [3] showed that the attenuation coefficient depends on the frequency, the surface tension, and the properties of the liquids, namely, viscosity and density. Such dependence suggests that this parameter can be used for identifying structural changes in the dynamic interfacial layer, which emerges in the case of the redistribution of chemically reactive components between phases of a heterogeneous liquid system [4].…”
mentioning
confidence: 93%